Development of a set of quality indicators in paediatric and perinatal care in Japan with a modified Delphi method - Shosuke Ohtera; Daisuke Shinjo; Hitoshi Kato; Yutaka Kanamori; Takashi Noguchi; Kimikazu Matsumoto; Nobuaki Ozawa; Naoya Nakadate (BMJ Publishing Group, 2023)
Backgrounds Few paediatric and perinatal quality indicators (QIs) have been developed in the Japanese setting, and the quality of care is not assured or validated. The aim of this study was to develop QIs in paediatric and perinatal care in Japan using an administrative database and confirm the feasibility and applicability of the indicators using a single-site practice test.Methods We used a RAND-modified Delphi method that integrates evidence review with expert consensus development. QI candidates were generated from clinical practice guidelines (CPGs) available in English or Japanese and existing QIs in nine selected paediatric or perinatal conditions. Consensus building was based on independent panel ratings. The performance of QIs was retrospectively assessed using data from an administrative database at the National Children's Hospital. Data between April 2018 and March 2019 were used, while data between April 2019 and March 2021 were also used for selected condition, considering the small number of patients. Each QI was calculated as follows: number of times the indicator was met/number of participants×100.Results From the literature review conducted between 2010 and 2020, 124 CPGs and 193 existing indicators were identified to generate QI candidates. Through the consensus-building process, 133 QI candidates were assessed and 79 QIs were accepted. The practice test revealed wide variations in the process-level performance of QIs in four categories: patient safety: median 43.9% (IQR 16.7%-85.6%), general paediatrics: median 98.8% (IQR 84.2%-100%), advanced paediatrics: median 94.4% (IQR 46.0%-100%) and advanced obstetrics: median 80.3% (IQR 59.6%-100%).Conclusions We established 79 QIs for paediatric and perinatal care in Japan using an administrative database that can be applied to hospitals nationwide. The practice test confirmed the measurability of the developed QIs. Benchmarking these QIs will be an attractive approach to improving the quality of care.